Foot Slab in Acute Fracture of Metatarsal Bone - Wongkraivet, Saroj (Journal of Health Science of Thailand, 2017)
The objective of this descriptive prospective study was to investigate the effectiveness of an alternative treatment for patients with acute fracture of metatarsal bone(s). Normally, short leg cast or short leg slab is applied to patients who have minimal displacement in metatarsal bone fractures in Chon Buri Hospital. Foot slab, a foot-long slab, was introduced as another innovative alternative to treat acute fracture metatarsal bone(s). The research on such foot slab for 37 patients extended from April 1, 2010 to March 31, 2011. After the application of foot slabs, patients reported less pain as measured by the differences of the average pain score. The immediate reduction from 6.46 to 3.64 was reported and further reduced to 2.27 in week 2, 1.42 in week 4 and 0.45 in week 8. From the radiograph, fractures of metatarsal bone(s) were healed on average, within 8 weeks and there was no complication on skin. Moreover the foot slab expense cost only 38 percent (62/165) of short leg cast and only 12 percent (62/514) of short leg slab (splint roll).